Defective trained immunity in patients with STAT-1-dependent chronic mucocutaneaous candidiasis. (7th July 2015) - Ifrim, D C; Quintin, J; Meerstein-Kessel, L; Plantinga, T S; Joosten, L A B; van der Meer, J W M; van de Veerdonk, F L; Netea, M G
Summary: Patients with signal transducer and activator of transcription-1 ( STAT1 )-dependent chronic mucocutaneous candidiasis (CMC) and patients with STAT3 -dependent hyper-immunoglobulin (Ig)E syndrome (HIES) display defects in T helper type 17 (Th17) cytokine production capacity. Despite this similar immune defect in Th17 function, they show important differences in the type of infections to which they are susceptible. Recently, our group reported differential regulation of STAT-1 and STAT-3 transcription factors during epigenetic reprogramming of trained immunity, an important host defence mechanism based on innate immune memory. We therefore hypothesized that STAT1 and STAT3 defects have different effects on trained immunity, and this may partly explain the differences between CMC and HIES regarding the susceptibility to infections. Indeed, while trained immunity was normally induced in cells isolated from patients with HIES, the induction of innate training was defective in CMC patients. This defect was specific for training with Candida albicans, the main pathogen encountered in CMC, and it involved a type II interferon-dependent mechanism. These findings describe the role of STAT-1 for the induction of trained immunity, and may contribute to the understanding of the differences in susceptibility to infection between CMC and HIES patients. This study could also provide directions for personalized immunotherapy in patients suffering from these immunodeficiencies.